Evaluasi Website Repositori Institusi Universitas Surabaya - Ulum, Amirul (STAIN Ponorogo, 2015)
TheÂ developmentÂ ofÂ institutionalÂ repositoriesÂ (IRs)Â in Indonesia within the broader framework of open access has significant impact on preserving intellectual capital and scholarly communication. InstitutionalÂ repositoriesÂ playÂ aÂ fundamentalÂ roleÂ inÂ centralizing, preserving,Â andÂ makingÂ accessibleÂ institutionâsÂ intellectualÂ capital. Evaluation of the system is to determine the functionality the system to meet the users need. Using a descriptive analysis this study wants to evaluate institutional repositories of University of Surabaya. The result is usefull for institution to develop the repository systems.